SURGICAL OUTCOMES OF PLATE FIXATION FOR CLOSED SCAPULAR FRACTURES (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the outcomes of surgical fixation of closed scapular fractures using locking plates at Viet Duc University Hospital and Viet Tiep Friendship Hospital.Methods: A descriptive study prospective was conducted on 35 patients with closed scapular fractures treated with plate fixation at Viet Duc University Hospital and Viet Tiep Friendship Hospital from January 2023 to June 2025. Fracture characteristics were assessed using plain radiography and computed tomography and classified according to the AO/OTA classification system 2018. Surgical factors including patient positioning, surgical approach, number of plates and screws used, operative time, and intraoperative blood transfusion were recorded. Treatment outcomes were evaluated based on postoperative pain, wound healing, shoulder function assessed by the Constant-Murley score, and quality of life assessed by the EQ-5D-5L index at the final follow-up.Results: The prone position was most commonly used during surgery (65.7%), followed by the lateral position (34.3%). The most frequently applied surgical approaches were the modified Judet approach (37.1%) and the Brodsky approach (62.9%). Most fractures were fixed using a single locking plate, while complex fractures required double-plate fixation. The mean operative time was 48.7 ± 12.3 minutes. The majority of patients did not require intraoperative blood transfusion (88.6%). Postoperatively, pain levels decreased significantly, surgical wounds healed well, and the complication rate was low. At the final follow-up, shoulder function improved markedly, with most patients achieving good or excellent outcomes according to the Constant-Murley score. The EQ-5D-5L index also showed significant improvement, indicating favorable recovery in daily activities and quality of life.Conclusion: Surgical fixation of closed scapular fractures using locking plates provides favorable outcomes with short operative time, low complication rates, and good recovery of shoulder function and quality of life.
Keywords: Scapular fracture, plate fixation, locking plate, Constant-Murley score, EQ-5D-5L.